Spectrofluorometric Determination of Baricitinib in Pure Form and Application on Pharmaceutical Dosage Form; Green Profile Evaluation via Eco-scale and GAPI Tools. - Ahmed Saleh; Nermin Victor; Amira Elkosasy (Archives of Pharmaceutical Sciences Ain Shams University, 2022)
FDA approved Baricitinib for the treatment of COVID-19 for hospitalized patients. So far, there is no previously published spectrofluorometric method for the analysis of Baricitinib. To this purpose, a first spectrofluorometric method with environmentally friendly approach for the determination of baricitinib in its pure and tablet dosage form has been developed and validated. The spectrum of BCT in methanol shows λex at 224 nm and λem at 414 nm. Calibration graph was found to be linear (r= 0.9998) over the concentration range of (0.500-1.000 μg/mL). The proposed method was validated with percentage recovery of 100.32 % ± 1.284 and relative standard deviation of less than 2.00 demonstrated the accuracy and precision of the method. The method was found to have a LOD of 0.102 μg and a LOQ of 0.309 μg⁄mL respectively. The study established showed that the proposed method can be adopted in the routine analysis since there is no specific monograph available in official pharmacopoeia up to this date for determination of Baricitinib.